(untitled) (Research, Society and Development, 2020)
Objective: to analyze the occurrence of Histoplasma capsulatum in cultures for fungi that were admitted to a State Public Health Laboratory in the Midwest of Brazil in the period from 2016 to 2019. Methodology: This is a cross-sectional study, consisting of cultures for research of fungi that entered the referred laboratory and come from State Reference Hospitals. The variables analyzed were gender, age group, number of positive and negative cultures for Histoplasma capsulatum and clinical specimen used for analysis. Results: In the analyzed period, a total of 12,476 fungi cultures were reported, 2,262 were positive, of which 313 identified the presence of Histoplasma capsulatum. The percentage prevalence of this agent among the positive samples corresponded to 13.84, in the age groups of 31 to 40 years old (19.28), 41 - 50 years old (16.83) and 51 to 60 years old (14.60), with a higher prevalence in males and regarding clinical specimens from bone marrow (85.00), lymph node (64.29), ascitic fluid (42.86), blood (39.96) and abscess (33.33). When analyzing the prevalence ratio, he verified a possible association of histoplasmosis in patient samples, whose main biological matrices were blood 6.28 (6.04 - 11.89), bone marrow 5.72 (4.52 - 68.12) and lymph node (3.15 - 28.48). Conclusion: In view of the prevalence found, the relevance of the compulsory notification of this ringworm at national level is noted in order to improve monitoring to support measures that facilitate early diagnosis and adequate treatment.